Experimental and computational studies of Schiff bases derived from 4-aminoantipyrine as potential antibacterial and anticancer agents - Johana Zúñiga-Miranda; Rebeca González-Pastor; Saskya E. Carrera-Pacheco; Cristina Rodríguez-Pólit; Carlos Barba-Ostria; Antonio Machado; Linda P. Guamán; Christian D. Alcivar-León; Jorge Heredia-Moya (Discover Applied Sciences)
Abstract Schiff bases are organic compounds recognized for their biological activities, including antiviral, antibacterial, antifungal, and anticancer properties, making them promising candidates in medicinal chemistry. In this studio, a series of Schiff bases 3a–h derived from 4-aminoantipyrine and substituted cinnamaldehydes were evaluated in vitro against liver (HepG2) and thyroid (THJ29T) cancer cells, Gram-positive and Gram-negative multidrug-resistant bacteria, and biofilm-forming pathogens. Six compounds demonstrated anticancer activity, though some exhibited toxicity to non-tumor cells. Compounds 3b, 3f, and 3h showed notable anticancer potential, while 3f and 3h also exhibited strong antibacterial effects, with 3f being the most effective against multidrug-resistant bacteria strains. These Schiff bases also inhibit biofilm formation, suggesting their potential for treating biofilm-related infections. In-silico analyses of their ADME properties, global reactivity descriptors, and binding affinities corroborated these findings. The Schiff base 3f has a strong binding affinity for DNA gyrase and vitamin D receptor, suggesting potential mechanisms for its antibacterial and anticancer activities.